ANALYSIS OF FACTORS AFFECTING COCONUT PRODUCTIVITY IN DISTRICT PANJATAN, REGENCY OF KULON PROGO - Kurnia Wulandari; Rini Anggraeni; Sulistiya MP (Fakultas Pertanian, Universitas Janabadra, 2018)
This study aimed to determine: (1) productivity of coconut in Sub district Panjatan Kulon Progo , and (2) productivity influence factors of coconut. The basic method used in this research is descriptive analysis. The research location is determined by purposive sampling based on the highest productivity, there is in Sub district Panjatan, and they are on Bojong Village with the coconut varieties of Bojong Bulat and in Bugel Village which not used that varieties. Farmer respondent determined by the systematic random sampling method, they are 60 respondents. Data analyzed by: (1) Independent sample t test and (2) multiple linear regression function. The result showed that: 1) The coconut productivity in Sub Panjatan many as 15 178 grains per ha per year, bojong bulat coconut varieties in Bojong village have a productivity of 39.53 percent higher than the varieties not bojong bulat in Bugel village (2) factors that significantly affect the productivity of the coconut is the population coconuts per hectare, the amount of fertilizer, planting distance coconut, labor, education respondents, and Dummy, while the oil age, other plant populations instead of cocoa, cocoa plant populations, and the respondent's age had no significant effect.